GHAZWUL FIKRI DIGITAL DAN KECERDASAN BUATAN:KERANGKA ANALITIS INTEGRATIF SERTA PROSPEK PERSEPSIGENERASI MUSLIM INDONESIA - Zisca Marcellina Mukti; Himawan Bintoro (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2026)
The acceleration of artificial intelligence and algorithmic personalization has reshaped how young Muslims access religious and secular information, extending classical notions of ideological influence into digital environments. This qualitative study uses a sequential explanatory design to investigate digital ghazwul fikri, war of ideas mediated by algorithms, chatbots, and generative systems, among Indonesian millennial and Gen Z Muslims from an integrative Islamic perspective. Phase I, reported in this manuscript, combines critical discourse analysis of fourteen recent academic sources on AI ethics, technology acceptance in Islamic education, ghazwul fikri, intellectual education in hadith, learning media, knowledge integration, and interfaith AI ethics with synthesis of wahdatul ‘ulūm and contextualized algorethics. Document analysis reveals a persistent gap: no empirical qualitative study links AI mediated influence to ghazwul fikri among Indonesian Muslim youth while integrating Islamic epistemology. Phase I findings show that global AI ethics discourse emphasizes regulation and human rights without operationalizing Islamic integrative frameworks; ghazwul scholarship remains library based without algorithmic modalities; and religious perspective on ICT is quantitatively established but not extended to generative AI or value conflict. The study constructs a preliminary integrative analytical framework mapping classical ghazwul strategies to contemporary digital modes and proposes implications for researchers in Islamic studies and technology ethics. Phase II phenomenological inquiry with youth informants, designed to test perception and value conflict themes, will follow institutional ethics clearance and is not yet reported here.